Jaminan dalam Aqad Pembiayaan Muḍārabah Perbankan Syariah di Wilayah Surabaya - Ana Toni Roby Candra Yudha (Al Tijarah, 2015)
The Moral hazard and skill of costumer are fundamental problems in fi nancing of sharia bank by muarabah contract. In order to reduce the risk of that problems, sharia bank obliges the bail for granted loan. This research aims to know how the determination of bail included in contracts of fi nancing, especially in muarabah contract. The approach of this research is qualitative descriptive approach. The analytic result shows that the collateral in sharia bank is different from conventional bank, it doesn’t bail the credits but it bails muarib for not breaking the agreement. Therefore, if the muarib incurred economical losses without breaking the agreement, the bail can’t be confi scated.